Deliverable 1.7 Report on stakeholder interaction in year 4 and 5 - Buch, Erik; Fernández, Vicente; van der Meeren, Gro; Sørensen, Mathilde B.; Sandven, Stein; Beszczynska-Möller, Agnieszka; Sejr, Mikael K.; Higgins, Ruth; Tjernström, Michael; Pirazzini, Roberta; Asmi, Eija; Quegan, Shaun; et al. (Zenodo, 2021)
In the light of the COVID-19 restrictions on working and meeting conditions the INTAROS Stakeholder Task Team decided to concentrate stakeholder activities during the last two years of the project on: • Dialog meetings with relevant European Research Infrastructures • A survey among sensor and instrument manufacturers. • Meeting with representatives of national managing authorities. • Attending relevant virtual conferences, webinars and networking events wherever possible. Successful dialog meetings were performed with 12 European Research Infrastructures revealing a good insight in their Arctic engagement, strategies and priorities for in situ observation, data management, focus on best practices, technology development, cooperation and coordination among themselves, funding situation and willingness to engage in future Arctic Observing System. More than 100 sensor and instrument manufacturers were invited to respond to a web-based technology survey – disappointingly only 16 companies responded. The survey showed that there is a group of sensor and instrument manufacturers that have experience, capability and interest in participating in innovation of new technology in the harsh Arctic environment. The marine and maritime management authorities expressed great interest in gaining environmental data from the Arctic region. Especially time series and trends are of importance, but also data in support of reliable ecosystem modelling was highlighted. The INTAROS achievements have been broadly promoted by the consortium members at conferences, workshops, webinars etc. primarily via virtual technology whereby the personal contact and networking has been lost. Some relevant events have been postponed or cancelled, so the outreach activity has not been so high as in the early part of the project.